2021
DOI: 10.1016/j.synbio.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between the nasopharyngeal microbiome and metabolome in patients with COVID-19

Abstract: SARS-CoV-2, the causative agent for COVID-19, infect human mainly via respiratory tract, which is heavily inhabited by local microbiota. However, the interaction between SARS-CoV-2 and nasopharyngeal microbiota, and the association with metabolome has not been well characterized. Here, metabolomic analysis of blood, urine, and nasopharyngeal swabs from a group of COVID-19 and non-COVID-19 patients, and metagenomic analysis of pharyngeal samples were used to identify the key features of COVID-19. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
48
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 55 publications
14
48
3
3
Order By: Relevance
“…S6a). Consistent with a previous study 35 , we found no significant differences between COVID-19 patients and Non-COVID-19 controls in the nasopharyngeal microbiome samples (Fig. 3a and Fig.…”
Section: Alterations Of the Human Microbiome In Covid-19 Patientssupporting
confidence: 93%
See 1 more Smart Citation
“…S6a). Consistent with a previous study 35 , we found no significant differences between COVID-19 patients and Non-COVID-19 controls in the nasopharyngeal microbiome samples (Fig. 3a and Fig.…”
Section: Alterations Of the Human Microbiome In Covid-19 Patientssupporting
confidence: 93%
“…Coherently, the human gut microbiome of patients with COVID-19 in our study exhibited decreased alpha diversity at the nrMAGs level compared to the Non-COVID-19 healthy controls. Although we did not found significant differences between patients with COVID-19 and Non-COVID-19 controls in two nasopharyngeal microbiome data sets, this may be due to the small sample size and the fact that Non-COVID-19 controls are not health controls 35 . Notably, our analysis identified that patients with COVID-19 after recovery (negative for SARS-CoV-2 via RT-qPCR) differed more from Non-COVID-19 controls compared to patients with COVID-19 before recovery.…”
Section: Discussioncontrasting
confidence: 69%
“…In terms of the association of the upper respiratory tract microbiome and SARS-COV-2 infection, the studies performed to date have included small cohorts of patients. Braun et al [37] (n=33), De Maio et al [38] (n=40), and Liu et al [39] (n=9) showed no significant differences in the nasopharyngeal microbial community between COVID-19 and control patients using α-β diversity and taxonomic compositional analysis. Whereas Mostafa et al [40] (n=50) and Engen et al [41] (n=19) reported a lower α diversity (Chao1, Shannon, and Simpson indexes) in COVID-19 compared to healthy patients, and both groups showed significant dissimilarities in β diversity.…”
Section: Discussionmentioning
confidence: 92%
“…In terms of the association of the upper respiratory tract microbiome and SARS-COV-2 infection, the studies performed to date have included small cohorts of patients. Braun et al [30] (n=33), De Maio et al [31] (n=40), and Liu et al [32] (n=9) showed no significant differences in the nasopharyngeal microbial community between COVID-19 and control patients using α-β diversity and taxonomic compositional analysis. Whereas Mostafa et al [33] (n=50) and Engen et al [34] (n=19) reported a lower α diversity (Chao1, Shannon, and Simpson indexes) in COVID-19 compared to healthy patients, and both groups showed significant dissimilarities in β diversity.…”
Section: Discussionmentioning
confidence: 96%